“Implementasi Good Governance Dalam Pengelolaan Sampah” - dan Rustan A, Maria Agustini Permata Sari (Jurnal Borneo Administrator, 2009)
If we cannot reduce the waste that we produce, automatically, it will be accumulated in a very great amount and will always be a problem, especially when we are not handling it well. The optimalization of waste management such as the handling and reduction of waste will not work properly if they are not supported and  being held together. Realizing a good governance by involving its three main pillars i.a. government, private sector and society in waste management is going to be a very effective way to create a clean, neat and healthy area/environment.  Keywords : Good Governance, Waste Management